1998
DOI: 10.1111/j.1469-8749.1998.tb15400.x
|View full text |Cite
|
Sign up to set email alerts
|

A patient with autistic disorder and a 20/22 chromosomal translocation

Abstract: The case history of a 3‐year‐old boy without speech and who met 10 criteria of an autistic condition (DSM‐IV) (American Psychiatric Association 1994) is reported. Psychometric evaluation, excluding the verbal scale, resulted in an IQ score of 56. The cytogenetic study showed a 20/22 translocation and an interstitial deletion within the region 22q11: 45, XY, ‐22, +der(20), t(20;22) (q13.3;q11.2), which was confirmed by fluorescence in situ hybridisation (FISH). Although deletions at 22q.11 are responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A 3 year old boy with muteness, who met DSM-IV criteria for autism, was found to have a 20/22 chromosomal translocation with an interstitial deletion within the 22q11 region; his phenotype was inconsistent with the DiGeorge syndrome. A 99mTc HMPAO brain perfusion SPECT showed a hypoperfusion of the left temporoparietal cortex in this boy (Carratala et al 1998). Although more than 30 genes have been identified in these deleted segments, neither a single gene or multiple contiguous genes have been identified as yet as responsible for these syndromes (Yamagishi 2002).…”
Section: The 22q11 and 22q13 Regionsmentioning
confidence: 69%
“…A 3 year old boy with muteness, who met DSM-IV criteria for autism, was found to have a 20/22 chromosomal translocation with an interstitial deletion within the 22q11 region; his phenotype was inconsistent with the DiGeorge syndrome. A 99mTc HMPAO brain perfusion SPECT showed a hypoperfusion of the left temporoparietal cortex in this boy (Carratala et al 1998). Although more than 30 genes have been identified in these deleted segments, neither a single gene or multiple contiguous genes have been identified as yet as responsible for these syndromes (Yamagishi 2002).…”
Section: The 22q11 and 22q13 Regionsmentioning
confidence: 69%
“…In our patient, the deletion could be either the result of manipulation or a sporadic event not directly related to IVF. Unbalanced translocations involving monosomy 22pterq11 in a 45 chromosome constitution have been described in association with 22q11.2 deletion [Back et al, 1980;Kelley et al, 1982;Faed et al, 1987;Jancar and Karki, 1989;Reddy et al, 1996;Jaquez et al, 1997;Carratalá et al, 1998;Damatova et al, 2009;Dundar al., 2009;McGoey and Lacassie, 2009;Shuib et al, 2009;Zrnová et al, 2012;Hu et al, 2014], none of these with a proven LCR 22q11.2 breakpoint. Our patient showed a breakpoint within the LCR-B, which has AT-rich palindromic sequences frequently involved in constitutional translocations, such as in the recurrent translocation t(11; 22) (q23;q11.2) [Gotter et al, 2004;Kato et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the interstitial deletion on chromosome 22q11 have also shown variable results. Carratalá et al 1998 examined a 3‐year‐old boy with autism and found a 20/22 translocation and interstitial deletion in 22q11. Roubertie et al 2001 also examined a child with deletion 22q11 who was diagnosed as autistic.…”
Section: The Conundrum Of Polygenicity and Autismmentioning
confidence: 99%